Archean geodynamics: Ephemeral supercontinents or long-lived supercratons - Liu, Yebo; Mitchell, Ross N.; Li, Zheng-Xiang; Kirscher, Uwe; Pisarevsky, Sergei A.; Wang, Chong (GEOLOGICAL SOC AMER, INC, 2021)
Many Archean cratons exhibit Paleoproterozoic rifted margins, implying they were pieces of some ancestral landmass(es). The idea that such an ancient continental assembly represents an Archean supercontinent has been proposed but remains to be justified. Starkly contrasting geological records between different clans of cratons have inspired an alternative hypothesis where cratons were clustered in multiple, separate “supercratons.” A new ca. 2.62 Ga paleomagnetic pole from the Yilgarn craton of Australia is compatible with either two successive but ephemeral supercontinents or two long-lived supercratons across the Archean-Proterozoic transition. Neither interpretation supports the existence of a single, long-lived supercontinent, suggesting that Archean geodynamics were fundamentally different from subsequent times (Proterozoic to present), which were influenced largely by supercontinent cycles.